2016
DOI: 10.1136/bmjgh-2016-000188
|View full text |Cite
|
Sign up to set email alerts
|

How prevention of violence in childhood builds healthier economies and smarter children in the Asia and Pacific region

Abstract: Investments in preventing violence against children in the Asia and Pacific region will bring important social and economic returns that contribute to building the region's ‘cognitive capital’. An analysis of burden of violence research in the region is presented to identify the impacts of violence and to demonstrate these returns. Violence is an everyday experience in the lives of many children in the Asia–Pacific, and the toxic stress associated with such routine forms of violence may permanently impact the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…Several studies have demonstrated the burden of early experiences of violence on health and other outcomes. Fry and Blight 16 recently found that different types of violence experienced during childhood contributes significantly to proportions of mental disorders in the Asia and Pacific region. The study also found that preventing VAC could help to reduce a wide range of risk behaviours (eg, teenage pregnancy in girls and use of illicit drugs in adolescence and adulthood).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the burden of early experiences of violence on health and other outcomes. Fry and Blight 16 recently found that different types of violence experienced during childhood contributes significantly to proportions of mental disorders in the Asia and Pacific region. The study also found that preventing VAC could help to reduce a wide range of risk behaviours (eg, teenage pregnancy in girls and use of illicit drugs in adolescence and adulthood).…”
Section: Introductionmentioning
confidence: 99%
“…Previous burden of violence against children studies have found significant impacts on children’s and adults’ mental and physical health, employment and education, as well as increasing risk factors for experiencing other forms of violence [ 1 ]. A burden study in the East Asia and Pacific region found that violence against children costs the region 2% of their GDP [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…High-quality birth-to-five programs for disadvantaged children can deliver a 13% per year return on investment (García, Heckman, Leaf, & Prados, 2016). Another review has shown that violence against children in China can lead to health consequences and productivity losses that may cost the country upwards of $101 billion U.S., equal to 1.7% of GDP (Fang et al, 2015;Fry & Blight, 2016).…”
Section: Returns On Investmentmentioning
confidence: 99%
“…In highincome countries, exposure to violence is associated with reduced intellectual functioning and academic achievement (Gilbert et al, 2009;Jonson-Reid, Drake, Kim, Porterfield, & Han, 2004;Lansford et al, 2002). Violence against children may reduce learning and behavioral, social, and emotional functioning (Fry & Blight, 2016).…”
Section: Returns On Investmentmentioning
confidence: 99%